2020
DOI: 10.1111/and.13926
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Feijoa sellowianan fruit on testicular toxicity‐induced by cadmium chloride

Abstract: Cadmium chloride (CdCl 2) as an environmental and industrial toxin has a significant detrimental effect on the testis (Nna et al., 2017). CdCl 2 is in the heavy metal group that is primarily released from colour pigments, TV screens, plating, battery manufacturing, plastics and fertilisers, and mining activities (Saini & Dhania, 2020). This combination enters the human body through contaminated food, drinking water and inhalation of air containing CdCl 2 particles or smoke containing CdCl 2 due to occupational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
1
5
0
1
Order By: Relevance
“…Our study demonstrated decreased testosterone, LH, and FSH levels in the Cd-exposed rats, findings that agree with previously published data on the effect of CdCl 2 on the pituitary-gonadal axis by Nna et al (2017) , Wang et al (2021) , and Horri et al (2021) . The reduced FSH levels could be explained by Cd-induced apoptosis in the anterior pituitary cells in a dose-dependent manner ( Yang et al , 2005 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study demonstrated decreased testosterone, LH, and FSH levels in the Cd-exposed rats, findings that agree with previously published data on the effect of CdCl 2 on the pituitary-gonadal axis by Nna et al (2017) , Wang et al (2021) , and Horri et al (2021) . The reduced FSH levels could be explained by Cd-induced apoptosis in the anterior pituitary cells in a dose-dependent manner ( Yang et al , 2005 ).…”
Section: Discussionsupporting
confidence: 93%
“…The percentage of motility in spermatozoa was calculated, a hemocytometer lam performed sperm counting, and the viability of spermatozoa was evaluated by cell membrane integrity following the criteria provided by the WHO. The assessment of sperm morphology was qualitative and quantitative and included microscopic evaluation for atypical spermatozoa morphology involving any changes involving the head, neck, mid-piece and tail and the diagnosis of abnormal spermatozoa ( Horri et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Disturbed gonadal and hormonal functions are also postulated to play a crucial role in the testicular toxicity induced by cadmium. Previous studies have described that several substrates that can regulate steroidogenesis and exert therapeutic effects on cadmium-induced testicular toxicity, such as Feijoa, Shilajit and Moringa leaf ethanolic extracts [ 6 , 28 , 29 ]. The present study was conducted to evaluate the effect of cadmium on steroidogenesis, the quality and quantity of sperm, and the inflammatory response in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Disturbed gonadal and hormonal functions are also believed to play a crucial role in the testicular toxicity induced by cadmium. Several studies have reported that several substrates that can regulate steroidogenesis can have therapeutic effects on cadmium-induced testicular toxicity, such as Feijoa, Shilajit and Moringa leaf ethanolic extracts [6, 23,24]. The present work was undertaken to evaluate the effect of cadmium on steroidogenesis, the quality and quantity of sperm, and the in ammatory response in mice.…”
Section: Discussionmentioning
confidence: 99%